Germination and fungi incidence in Cerejeira-da-mata seeds at different fruit maturation levels and temperatures - Lovatto, Maike; Baseggio, Ediane Roncaclio; Lugaresi, Adriana; Girardi, Gian Carlos; Uberti, Alison; Giacobbo, Clevison Luiz (Agrarian, 2021)
The effect of different levels of physiological maturation of the fruit and temperature on the seed germination and incidence of fungi that are harmful to the seeds, becomes fundamental for the improvement of the propagation of different native fruit species. The objective of this work was to evaluate the effect of physiological maturation and temperature on the germination and fungi incidence in Eugenia involucrata DC. seeds. Three experiments were carried out. In the experiment I, the effect of four levels of physiological maturation was evaluated, visually determined based on the color of the fruit, and in the experiment II, was evaluated the effect of two levels of maturation and two temperatures (25 and 35 °C) on the germination and vigor of the seeds. In the experiment III, was investigated the incidence of fungi in the seeds at two temperatures (25 and 35 °C). The levels of maturation evaluated did not influence the percentage of germinated seeds, but they influenced seed vigor. The temperature of 25°C was suitable for seed germination. The fungi genera found on the seeds were Trichoderma, Aspergillus, Fusarium, Penicillium, Alternaria, and Colletotrichum with variable incidences depending on evaluated temperature.